L’indemnisation des victimes d’actes criminels : étude comparative - Rico, José (Acta Criminologica)

(untitled) (Les Presses de l'Université de Montréal, 1968)
AbstractCOMPENSATION TO VICTIMS OF CRIMINAL OFFENCESThe system of composition, which was developed during the Middle Ages, especially under Germanic penal law, represents not only an abatement of the system of collective vengeance characteristic of this era, but also the first step towards the principle of compensation to victims of criminal offences.With the development and consolidation of a strong central power, the State asked for a share of these transactions either in the form of sanction or as a price for its intervention. W^hen at last the central government obtained the full and exclusive right to inflict punishment and when private justice gave way to public justice, the State's share of compensation increased progressively and took the form of fines, while the victim's share gradually diminished and withdrew little by little from the penal system to become civil compensation for damages.Nevertheless, the total separation between public action, whose aim is to ensure punishment, and civil action, whose main object is to secure compensation to the victim, did not materialize until very recently. This principle of total separation, which was adopted by the classical schoolof criminal law, resulted in a complete overlooking of the victim's right to compensation, in daily legal practice.New solutions were therefore proposed to remedy this deficiency in the penal systems, the most original and daring being those to be found in the Spanish Penal Codes of 1822 and 1848 which compel the State to compensate victims of criminal offences when the wrong-doers or other responsible persons are unable to do so.This idea of compensation by the State to victims of crime, although taken lip and elaborated several years later by Bentham and the Italian Positivist School, had absolutely no repercussions as far as practice was concerned. It was only in the second half of the XXth Century that an Englishwoman, Margaret Fry, drew the attention to this problem. Inspired by her compatriot Bentham, Margaret Fry proclaimed that compensation for harm caused to victims of criminal violence should be assumed by the State.This was the starting point of a considerable development in the study of compensation to the victim. During the last ten years, not only were many papers and conferences devoted to the subject, but also many legislations adopted the progressive solution of conferring upon the State the task of compensating the victim of criminal offences.In most contemporary penal legislations, the dissociation between public and civil action has resulted in relegating the subject of compensation solely to the civil domain.A certain number of penal systems (France, Belgium, Germany, etc.), while accepting in principle the civil character of this matter, nevertheless offer the injured party the possibility of bringing his action for damages before criminal courts.A last group of systems (Spain, Italy, Switzerland) treat this problem within the framework of the criminal code, although in most cases they do nothing but repeat analogous paragraphs of the civil code.Upon examining these different methods of coping with the problem of compensating the victim for damages caused by criminal violence, we find that certain reforms were put into effect but that they chiefly hinge upon one preliminary question ~— the means available to the victim for bringing his case before the criminal courts and of engaging in the criminal procedure, to obtain recognition of his rights by the Court.However, it often happens that once the sentence has been passed, the victim is obliged to act on his own to recover the sum of the indemnity. Modern penal law, progressive and innovating as it is in certain respects, often neglects the victim of crime.Certain solutions were proposed and even introduced into positive penal legislations, in view of securing for the injured party, as much as possible, the recovery of the compensation decided upon by the courts in his favour, especially in cases where the offender is destitute.Among such solutions, one should stress legal solidarity between co-delinquents, priority accorded to the compensation debt, accessory imprisonment, compulsory work in prison and in liberty, compulsory insurance and the creation of a compensation fund. Similar proposals tend to consider compensation to the victim as an indispensable condition for the obtainment of certain privileges (pardon, parole, probation, legal rehabilitation, etc.).Due to the insufficiency of the classical systems and of the solutions destinated to secure compensation of the victim by the offender, one again began to wonder whether the State should not undertake the charge of repairing damages caused by crime.The main argument offered in favour of this system is the State's failure in preventing crime and in protecting its citiiens against felonious acts.Despite the numerous criticisms concerning the essentially judicial composition of the courts in charge of the application of the system as well as of the procedure to be followed, the infractions to be compensated, the amount to be paid and the total cost of the system, some countries have recognized the right of the victim to be compensated and consequently adopted measures to enforce this principle (New Zealand, 1963; GreatBritain, 1964; States of California and New York, 1966; the Canadian province of Saskatchewan, 1967).